Depression, suicide intent, and plan among adults presenting in an emergency department after making a suicide attempt: Exploratory differences by psychosis symptom experience. (January 2023) - Bornheimer, Lindsay A.; Wastler, Heather; Li Verdugo, Juliann; Im, Vitalis; Burke, Heather; Holzworth, Joshua; Velasquez, Emma; Mahmood, Muminah
Abstract: Rates of suicide are significantly higher for individuals with schizophrenia spectrum disorders (SSDs) than those in the general population. With limited understandings of factors contributing to engaging in a suicide attempt among the psychosis population in the literature, the current study sought to preliminarily explore depression, suicide intent, and suicide plan among adults with and without psychosis symptom experiences who presented to an emergency department (ED) after making a suicide attempt. Electronic health record data were collected from the ED of an academic healthcare system in the Midwestern United States between 2011 and 2022. Patients included 1178 adults who arrived after making a suicide attempt. Trained research assistants conducted chart reviews and data were explored in SPSS28. A significantly smaller proportion of patients with psychosis had depressive symptoms and endorsed having suicide intent prior to their attempt in comparison to patients without psychosis. A smaller trending (p < .10) proportion of patients with psychosis endorsed having a suicide plan prior to their attempt than those with psychosis. Exploratory findings highlight the importance of EDs assessing for suicide risk beyond traditional approaches among patients with psychosis symptom experiences, including considerations for the potential of individuals not experiencing depression, suicide intent, or a suicide plan. Future research is particularly needed to examine psychosis symptomatology and the experience of distress as potential contributing factors to suicide behavior and death among patients with psychosis symptoms to better inform suicide risk assessment and intervention efforts.